Myocardial Fibrosis in Hypertrophic Cardiomyopathy. Issue 5 (September 2015) - Langer, Christoph; Schaefer, Philipp; Lutz, Matthias; Eden, Matthias; Hohnhorst, Mirko; Harders, Hauke; Faber, Lothar; Jansen, Olav; Both, Marcus; Frey, Norbert
<x xml:space="preserve">Abstract</x> Introduction With subgroups of patients with hypertrophic cardiomyopathy (HCM) confers a 4% to 5% risk for adverse prognosis. Besides left-ventricular muscle mass (LV-MM) myocardial fibrosis (MF) assessable by late gadolinium enhancement in cardiovascular magnetic resonance (LGE-CMR) has been related to that. Myocardial fibrosis can also be demonstrated by late enhancement (LE) in late-enhanced multislice computed tomography (leMDCT). This analysis investigates leMDCT whether to enable quantification of LE load in terms of LE mass by percent LV-MM in HCM. Methods In a prospective validation study, we included 30 consecutive patients with HCM who underwent leMDCT (64 slice) and LGE-CMR (1.5 T). The leMDCT scan was performed 7 minutes after injection of iodine contrast (Iopromid). Endocardial and epicardial planimetry served for the assessment of LV-MM. Visually detectable LE was quantified using the manual quantification method resulting in LE by percent LV-MM (%LE). The LGE-CMR data served for validation. Results Mean (SD) age was 64.1 (13.9) years. Myocardial fibrosis prevalence was 63.3% (19/30 patients indentified by both leMDCT and LGE-CMR). In leMDCT, tissue density in LE areas compared with normal myocardium was higher (138.2 [23.9] HU vs 98.4 [16.5] HU, P < 0.001) but lower than in the LV cavity (138.2 [23.9] HU vs 169.2 [35.9] HU, P < 0.001). Late enhancement mass in leMDCT seemed to be 7.9 (8.5) g LE versus 8.6 [11] g LGE in CMR (P = 0.497, r = 0.95) resulting in a leMDCT/LGE-CMR relation of 1.2. Referring LE mass to LV-MM gave an LE proportion measured by leMDCT of 4 (3.9) %LE versus 3.9 (4.1) %LGE in LGE-CMR (r = 0.88, P = 0.75). Intraobserver/interobserver reliability of LE mass assessment showed an intraclass correlation coefficient of 0.99 and 0.97. Conclusions In patients with HCM, leMDCT provides volumetric assessment of LE mass—absolutely and by percent LV-MM.